Excoriation disorder: Impulsivity and its clinical associations. (March 2015) - Oliveira, Elen C.B.; Leppink, Eric W.; Derbyshire, Katherine L.; Grant, Jon E.
Highlights: We compared high impulsivity on the BIS-11 and SST neurocognitive task. High impulsivity on the BIS-11 predicted greater urges to pick. The SSRT did not show any differences in severity based on impulsivity level. High impulsivity on the BIS-11 also predicted higher depression and anxiety scores. Results may reflect that the SST and BIS-11 assess distinct aspects of impulsivity. Abstract: Excoriation disorder is the repetitive scratching or picking of skin that leads to physical damage, distress, and functional impairment. Skin picking has been associated with impulsivity and problems with inhibition. We hypothesized that problems in these areas could be disease severity markers. We recruited 73 adults meeting DSM-5 criteria for excoriation disorder, and 50 adult controls. Those with excoriation disorder were categorized as either "high impulsive" (HI) or "low impulsive" (LI) using either a neurocognitive task of motor impulsivity (Stop Signal Task) or the Barratt Impulsiveness Scale's (BIS-11) motor impulsivity subscale. The HI subjects, based on the BIS-11, showed higher urges scores, anxiety, and depressive symptoms. These data suggest that impulsivity may reflect a specific clinical presentation among those with excoriation disorder, but the clinical characteristics differ depending upon the impulsivity measure used. Agreement on how to measure various domains of impulsivity may be important in better understanding the disorder psychopathology and so improve future treatments.